Subwavelength Artificial Structures: Opening a New Era for Engineering Optics. Issue 4 (23rd November 2018) - Luo, Xiangang
Abstract: In the past centuries, the scale of engineering optics has evolved toward two opposite directions: one is represented by giant telescopes with apertures larger than tens of meters and the other is the rapidly developing micro/nano‐optics and nanophotonics. At the nanoscale, subwavelength light–matter interaction is blended with classic and quantum effects in various functional materials such as noble metals, semiconductors, phase‐change materials, and 2D materials, which provides unprecedented opportunities to upgrade the performance of classic optical devices and overcome the fundamental and engineering difficulties faced by traditional optical engineers. Here, the research motivations and recent advances in subwavelength artificial structures are summarized, with a particular emphasis on their practical applications in super‐resolution and large‐aperture imaging systems, as well as highly efficient and spectrally selective absorbers and emitters. The role of dispersion engineering and near‐field coupling in the form of catenary optical fields is highlighted, which reveals a methodology to engineer the electromagnetic response of complex subwavelength structures. Challenges and tentative solutions are presented regarding multiscale design, optimization, fabrication, and system integration, with the hope of providing recipes to transform the theoretical and technological breakthroughs on subwavelength hierarchical structures to the next generation of engineering optics, namely Engineering Optics 2.0. Abstract : As one of the cornerstones of the modern information society, engineering optics is faced with great challenges resulting from classic optical theories and materials. Based on subwavelength engineered structures, it is now possible to break through traditional performance limitations by replacing bulky and costly optical devices with extremely thin and lightweight components, which lays the foundation of the next generation of engineering optics.